Acute Effects of Myofascial Release on Foot Mobility and Performance in Basketball Players with Hypomobile Feet—A Randomized Controlled Trial - Nihat Sarıalioğlu (Life)
Hypomobility in the foot structure causes functional limitations. These functional limitations affect sportive performance negatively, especially in basketball, where dynamic movements such as jumping and sudden changes in direction are very intense. In this context, reducing hypomobility is important in terms of eliminating performance disorders caused by hypomobility. The purpose of this study was to investigate the acute effects of myofascial release on foot mobility and sportive performance in basketball players with hypomobile feet. This study was designed as randomized controlled experimental research. Twenty-four male basketball players (23.46 ± 2.81 years) participated in this study. The athletes were first subjected to foot mobility, balance and vertical jump tests. Then, the participants were divided into two groups: myofascial release (MR) and placebo myofascial release (PMR). Myofascial release (Graston technique) was applied to the MR group, and placebo myofascial release was applied to the PMR group. After application, foot mobility and performance measurements were performed again, and the results were analyzed. It was observed that there was a significant difference in right foot mobility (d = 4), left foot mobility (d = 6), vertical jump (d = 1.13) and dynamic balance (d = 1.03) parameters after application in the MR group. It was also determined that the acute effects of the intervention on foot mobility lasted for at least two hours (p < 0.001). There was no change in any parameter after application in the PMR group (p > 0.05). The results of this study show that a single session of myofascial release applied to the plantar sole temporarily increased foot mobility and improved vertical jump and dynamic balance performance in basketball players with chronic hypomobility.